2020
DOI: 10.1016/j.cej.2020.126015
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation kinetics of hercynite spinels for solar thermochemical fuel production

Abstract: The development of an economically viable solar thermochemical fuel production process relies largely on identifying redox active materials with optimized thermodynamic and kinetic properties. Iron aluminate (FeAl2O4, hercynite) and cobalt-iron aluminate (CoxFe1-xAl2O4) have both been demonstrated as viable redox-active materials for this process. However, doping with cobalt produces a qualitative tradeoff between the thermodynamic and kinetic properties of hercynite by improving the reaction kinetics although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 58 publications
0
11
1
Order By: Relevance
“…Importantly, the improved performance was consistent, as the presence of cobalt has been suggested to impede the diffusion of iron and thus prevent deactivation by sintering; 21 a later study reported stable performance over 200 cycles. 22 In addition, cobalt has been shown, using in situ X-ray photoelectron spectroscopy, to promote reduction at the cobalt–iron aluminate surface, 23 thereby increasing the thermodynamic driving force for subsequent oxidation. As a result, samples with higher cobalt content, when reduced under equivalent conditions, exhibit faster kinetics for the dissociation of both H 2 O 24 and CO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, the improved performance was consistent, as the presence of cobalt has been suggested to impede the diffusion of iron and thus prevent deactivation by sintering; 21 a later study reported stable performance over 200 cycles. 22 In addition, cobalt has been shown, using in situ X-ray photoelectron spectroscopy, to promote reduction at the cobalt–iron aluminate surface, 23 thereby increasing the thermodynamic driving force for subsequent oxidation. As a result, samples with higher cobalt content, when reduced under equivalent conditions, exhibit faster kinetics for the dissociation of both H 2 O 24 and CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, samples with higher cobalt content, when reduced under equivalent conditions, exhibit faster kinetics for the dissociation of both H 2 O 24 and CO 2 . 23 However, a trade-off between more rapid kinetics and higher product yields was also observed, 23 such that the largest quantities of H 2 and/or CO are obtained for the oxidation of reduced iron aluminates. Slower kinetics are generally associated with the presence of hercynite (FeAl 2 O 4 ), 25,26 a spinel phase that is only predicted to exist in samples that are cobalt deficient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main technological requirements for lowering the product cost in the thermochemical looping cycle include: (1) large thermodynamic equilibrium CO 2 /water splitting capacity (ref. 45; defined in Subsection 2.1) at feasible conditions, usually described as a large oxygen release from the oxide at a practical temperature and oxygen partial pressure ( p O 2 ), 46 and a high CO 2 /water conversion; (2) fast reaction kinetics that enables a short cycle time; 47–49 and (3) long-term cyclability of both the reactor and the redox material.…”
Section: Introductionmentioning
confidence: 99%
“…Spinel-type ferrites have attracted great attention due to its structural characteristics and potential applications, specially related to their magnetic properties. Spinel structured materials have FCC structure and general formula AB2O4 [1] and can be synthetized by several methods, including co-precipitation, sol-gel [2] and combustion reaction [3]. The latter is particularly convenient, even for nanoparticles, due the low cost, high reaction speed, that may take only a few minutes, and for being energetically efficient, because the reaction environment releases enough energy for the reaction to occur [4].…”
mentioning
confidence: 99%